2012
DOI: 10.1038/bmt.2012.77
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of early quality of life outcomes in autologous and allogeneic transplant patients

Abstract: The Functional Assessment of Cancer Therapy-Bone Marrow Transplant measures quality of life (QOL) in SCT patients. Prior reports found mixed results regarding QOL differences among autologous and allogeneic SCT patients. In addition, there is a paucity of literature examining differences in QOL patterns over time between autologous and allogeneic patients. The present study examines differences in QOL between patients free of clinical depression undergoing autologous (n ¼ 41) and allogeneic (n ¼ 64) SCT during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
11
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 26 publications
3
11
1
1
Order By: Relevance
“…This fact indicates that therapy had no influence in participants' emotional factor. In a study performed in Chicago (USA) with 105 cancer patients, the FACT-BMT scale results reached similar averages to those of the current study, between 18.85 and 20.52 (score 0-28) (12) . In a study developed in the cities of Heidelberg and Wiesbaden (Germany) and in a review also conducted in Germany, both using the QLQ-C30 scale, the results in the emotional function had negative scores in the three stages during the hospitalization period, which differs from this study (11,20) .…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…This fact indicates that therapy had no influence in participants' emotional factor. In a study performed in Chicago (USA) with 105 cancer patients, the FACT-BMT scale results reached similar averages to those of the current study, between 18.85 and 20.52 (score 0-28) (12) . In a study developed in the cities of Heidelberg and Wiesbaden (Germany) and in a review also conducted in Germany, both using the QLQ-C30 scale, the results in the emotional function had negative scores in the three stages during the hospitalization period, which differs from this study (11,20) .…”
Section: Discussionsupporting
confidence: 61%
“…However, a review performed in Germany with the main QOL studies using the QLQ-C30 to evaluate the pre-and post-HSCT (11) , and another review performed in Chicago (USA) that compared the QOL of patients undergoing autologous and allogeneic HSCT in 105 participants with cancer, showed the patients' age was between 40 and 50 years (12) , which differs from the present study findings. The marital status and number of children in this study corroborate data found in national and international literature, i.e., patients with hematological malignancies are married or in a common-law marriage and have one to three children (12)(13)(14)(15)(16) . In a study on the bond between cancer patients and their families, it was observed that the main companions of patients with neoplasia are children, spouses and parents, and family involvement is critical during the disease process.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…32 Nursing has the prerogative to be the team that is closest to and actively participates in treatment in its different phases. Thus, it should seek to fill this gap by inserting itself more and more into research that addresses this issue.…”
Section: Discussionmentioning
confidence: 99%